Dork Diaries:Tales From a Not-So- Happily Ever After - Russell, Rachel Renee (Simon & Schuster, Inc., 2013)
'Once upon a Dork$1! =(B''wait!why do all these fairy tale characters Nikki's running into seem so familiar$1! =(B?s
Keywords: Juvenile Fiction